Description of a Novel Technique to Address Both External Nasal Valve Collapse and the Aesthetic of the Nasal Tip - Rosario, Eleanor May; Ferguson, Mark; Machado, Poliana Batista; Saleh, Hesham (Facial Plastic Surgery, 2022)
Severe concavity of the lateral crura can lead to an unsightly aesthetic deformity of the nasal tip and narrowing of the external nasal valve. Concurrently, if the lateral crura are structurally weak, this can lead to a functional issue. We report a previously undescribed technique of combining a lateral crural reversal with a turn-in flap. This achieves dual goals of aesthetic improvement and structural reinforcement, without the need for grafting.
Keywords: lateral crural reversal; turn-in flap; external nasal valve collapse